Mobile applications in cultural heritage context: a survey - Silva, Manuel (2020)
Understanding the existing characteristics of smartphones in cultural heritage will increase our understanding of what has been created so far, where the potential of mobile technology may be the best use in the future. Thus, in this study, the authors systematically review existing smartphone apps dedicated to cultural heritage, particularly in museums, streets, and cities, available in app stores, to identify trends and current features with potential impact in new apps development. A second goal is to find and study applications with features such as GPS, Live Notifications, Map, Photos, Video, Audio, Games, Augmented Reality, combined into a single app